2003
DOI: 10.1080/0265204021000058410
|View full text |Cite
|
Sign up to set email alerts
|

Nanoprecipitation technique for the encapsulation of agrochemical active ingredients

Abstract: In 1997, a research programme was initiated to assess the ability of nanospheres (NS) to improve the biodelivery of a new insecticide to plants. Stable polymeric NS, with a size near 135 nm and an encapsulation rate in the range of 3.5%, have been obtained using a nanoprecipitation method with Eudragit S100 polymer. Biological studies have been performed on cotton plants infested with aphid, to estimate the direct contact efficacy of NS formulations on the insects and the systemicity of the encapsulated active… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(36 citation statements)
references
References 31 publications
0
30
0
1
Order By: Relevance
“…A few years later polymeric nanocapsules were described as vehicles for the pesticides ivermectin and acetamiprid [197], while Wang et al [198] used nanosized inorganic particles such as TiO 2 , SiO 2 , Fe 2 O 3 , or Al 2 O 3 as pesticide carriers for increased bioactivity and reduction in residues. Boehm et al [199] obtained stable polymeric nanospheres (135 nm) with 3.5% encapsulation rate and despite the low active ingredient content, this formulation yielded significant improvements in the bioavailability of the insecticide (RPA 107382) to plants. These researchers also performed biological studies on cotton plants infested with aphids to estimate the direct contact efficacy of nanosphere formulations on insects.…”
Section: Pesticide Delivery For Crop Protectionmentioning
confidence: 97%
“…A few years later polymeric nanocapsules were described as vehicles for the pesticides ivermectin and acetamiprid [197], while Wang et al [198] used nanosized inorganic particles such as TiO 2 , SiO 2 , Fe 2 O 3 , or Al 2 O 3 as pesticide carriers for increased bioactivity and reduction in residues. Boehm et al [199] obtained stable polymeric nanospheres (135 nm) with 3.5% encapsulation rate and despite the low active ingredient content, this formulation yielded significant improvements in the bioavailability of the insecticide (RPA 107382) to plants. These researchers also performed biological studies on cotton plants infested with aphids to estimate the direct contact efficacy of nanosphere formulations on insects.…”
Section: Pesticide Delivery For Crop Protectionmentioning
confidence: 97%
“…The formulation of any nano-fertilizer should be in such a way that they possess all desired properties such as high solubility, stability, effectiveness, time-controlled release, enhanced targeted activity with effective concentration, and less eco-toxicity with safe, easy mode of delivery and disposal (Tsuji 2001;Boehm et al 2003;Green and Beestman 2007;Torney et al 2007). Nanoparticles have great potential to deliver nutrients to specific target sites in living systems.…”
Section: Nano-fertilizer Formulations and Their Smart Delivery Systemsmentioning
confidence: 99%
“…Thus polycaprolactone and polylactic acid nanospheres (NS) were examined for the nanoencapsulation of the insecticide ethiprole (Bohem et al 2003). The authors concluded that NS did not provide a controlled release of the AI but, due to their small size, they enhance the penetration through the leaf and consequently boost the systemic activity relative to the classical SC formulations.…”
Section: Nanoformulations Of Crop-protection Chemicalsmentioning
confidence: 97%